TINJAUAN YURIDIS TINDAK PIDANA CYBERCRIME DALAM PERSPEKTIF HUKUM PIDANA - Eliza Oktaliana Sari (Kajian Hukum, 2018)
The development of information and communication technology have  big influence in various fields of life today. Starting from the 20th century, this development brought rapid changes in human life. The community has taken advantage of the advances in information and communication technology as a medium for doing business, even for political purposes. But because of the ease of creativity, many parties are not responsible for taking advantage of these opportunities for things that harm many people. Crimes that often occur today are in the form of Cybercrime, by entering, using computer facilities or computer networks without permission, against the law with or without causing changes, and or damage to the computer facilities that are entered or used. The perpetrator of the crime is not limited to age, which is territorially cross border crime.This paper intends to analyze the crime of cybercrime in the perspective of criminal law, and efforts that can be used to combat cyber crime, by using a normative juridical approach, namely research that explains the provisions in applicable laws and regulations, related to the reality in field. Then analyzed by comparing between the demands of the ideal values that exist in the legislation with the reality in the field. The results obtained indicate that a juridical review of criminal acts of cybercrime in criminal law in Indonesia has a variety of positive and negative impacts, originating from the Criminal Code and outside the Criminal Code, in accordance with conventional crime arrangements, as well as efforts that can be used to overcome crime of cybercrime. Keywords : Juridical Review, Cybercrime, Criminal Law.